Aplikasi Post Structuralism Pada Perancangan Fakultas Ilmu Keperawatan Universitas Riau - Risperdana, Risperdana; Firzal, Yohannes; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Post Structuralism on development has a purpose to emphasize architecture in terms of construction and structure and has an aesthetic value based on form expressions. Application of the post structuralism to show the structure as an aesthetic building and make it as a mass of building. In appropriate with the theme of post structuralism, design the Faculty of Nursing University of Riau apply the form based on the expression. It is because the unavailability of building that can be able to accommodate lecture activities and form that applies function expression like a make structure as core design and give a character to building, so that functions communicated with the form can deliver various expressions with the protrusion of the structure as the main element. Using the concept of Tri Dharma Perguruan Tinggi like form of describe three pillar which to connecting and make as base on pattern mass of building and apply of Post Structuralism which make a structure as a mass builder and like as core design. Keywords: Post Structuralism, Ekspression, Form